Protective effect of Astragaloside IV on chronic intermittent hypoxia-induced vascular endothelial dysfunction through the calpain-1/SIRT1/AMPK signaling pathway - Zhao, Fang; Meng, Yan; Wang, Yue; Fan, Siqi; Liu, Yu; Zhang, Xiangfeng; Ran, Chenyang; Wang, Hongxin; Lu, Meili (Frontiers in Pharmacology, 2022)
Vascular endothelial dysfunction (VED) is linked with the pathogenesis of obstructive sleep apnea (OSA) comorbidities, such as cardiovascular disease. Astragaloside IV (As-IV) has exhibited significant improvement for endothelial dysfunction. Nonetheless, the protective mechanism is not clear. Therefore, the present study investigated the potential mechanism of As-IV on VED. Calpain-1 knockout and wild-type C57BL/6 mice exposed to chronic intermittent hypoxia (CIH) were established and treated with As-IV (40, 80 mg/kg) for 4 weeks. Human coronary artery endothelial cells (HCAECs) subjected to CIH exposure were pretreated with As-IV, MDL-28170 (calpain-1 inhibitor) and SRT1720 (SIRT1 activator) for 48 h in vitro. The endothelial function, inflammation, oxidative stress and mitochondrial function were measured to evaluate VED. Our data revealed that As-IV treatment ameliorated CIH-induced endothelial-dependent vasomotion and augmented nitric oxide (NO) production. As-IV administration suppressed the secretion of inflammation, oxidative stress and mitochondrial dysfunction. As-IV treatment reduced the expression of calpain-1 and restored the downregulated expression of SIRT1 and Thr172 AMPK and Ser1177 eNOS phosphorylation. The effects of calpain-1 knockout and SRT1720 were similar to the effect of As-IV on VED. These findings demonstrated that As-IV ameliorated VED induced by chronic intermittent hypoxia via the calpain-1/SIRT1/AMPK signaling pathway.